Investigating the co-development of academic competencies and educational aspirations in German primary education - Bittmann, Felix (Frontiers in Education, 2022)
Academic achievement and educational decisions, which are strongly related to primary and secondary effects, are the two main drivers behind the emergence of social inequality in education. To understand this process in more detail, even before final decisions have to be made, the reciprocal influence of achievement and aspirations is of greatest interest. By not simply looking at an ultimate outcome but investigating its antecedents in a longitudinal fashion over the course of multiple years more insight is gained. Using German large-scale NEPS panel data, it is possible to demonstrate this co-development quantitatively. Cross-lagged panel models are utilized to show that the achievement in mathematics (measured by comprehensive achievement tests) and parental realistic aspirations influence each other positively in a statistically significant way over the course of primary education from grade one to four, even under the control of various potential confounding variables. Further analyses reveal that this process is socially stratified and works differently for lowly and highly educated families. Lower educated parents pay more attention to the performance of the child when adjusting their aspirations than tertiary educated parents, who always hold high aspirations. The results are of interest to understand in more detail how social inequality emerges at a very early point in the highly tracked German educational system.